Cultural Beliefs and Practices for Pregnant Women in Society Ducurai Village, Administrative Post, Ermera Municipality in 2024 - Do Carmo, Joana Genia Ledia Neves; Syarifudin, Muhammad; Umamity, Syahfitrah (UNIMUS Web Conferences, 2026)
Background: Cultural beliefs and traditional practices play an important role in shaping maternal health behaviors in many communities, particularly in developing countries. In Timor-Leste, ancestral traditions remain influential in guiding pregnancy-related practices, including decisions regarding place of delivery and maternal care. Objective: This study aimed to explore the cultural beliefs and practices related to pregnancy among women in Ducurai Village, Letefoho Administrative Post, Ermera Municipality. Method: This study employed a qualitative research design conducted from August to September 2024. The participants consisted of ten pregnant women selected using a non-probability sampling technique. Data were collected through observation, in-depth interviews, and documentation using interview guidelines developed by the researchers. The collected data were analyzed descriptively to identify patterns of cultural beliefs and practices among pregnant women. Results: The findings revealed that the majority of respondents strongly believed in and practiced cultural traditions inherited from their ancestors. These traditions influence various aspects of pregnancy-related behavior and are maintained as part of community identity and social values. Cultural beliefs were perceived to provide guidance and protection for both mothers and their unborn children. Conclusion: Cultural beliefs and traditional practices remain important factors influencing pregnancy-related behaviors in Ducurai Village. Therefore, culturally sensitive maternal health interventions are necessary to promote safe pregnancy practices while respecting local traditions and community values.